PENGARUH KELENGKAPAN FASILITAS PEMBELAJARAN TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP NEGERI 10 PEMATANGSIANTAR TAHUN AJARAN 2021/2022 - Dianti Siboro, Thiur; Saragih, Marlindoaman; Winata Purba, Sukma (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2022)
This study aims to determine the effect of the completeness of learning facilities on the science learning outcomes of seventh-grade students of SMP N. 10 Pematangsiantar in the 2021/2022 academic year. The population in this study was 224 students and a sample of 35 students. The sampling technique used was random sampling, taking 15% from classes VII-1 to VII-7. The variables in this study were independent variables and dependent variables. In this study, the independent variable (X) was the completeness of learning facilities and the dependent variable (Y) was the science learning outcomes of seventh-grade students of SMP Negeri 10 Pematangsiantar. The analysis techniques used were validity and reliability tests, correlation tests, and hypotheses were proven using the t-test at a significance level of α = 0.05. The average score of students' science learning outcomes was 80.2, which is a high average learning outcome. The average score of the questionnaire on the completeness of science learning facilities for grade VII students of SMP N.10 Pematangsiantar was 73.43, which is a fairly high average. From the results of the correlation test, the correlation between the completeness of learning facilities and the science learning outcomes of grade VII students of SMP N.10 Pematangsiantar in the 2021/2022 academic year was obtained r = 0.81. Based on the qualification of the correlation coefficient, the correlation between the two variables above is a very high correlation. From the results of the hypothesis testing/with the t-test, the t-count = 8.03 was obtained and at a significance level of ∝ = 0.05 and dk = 33, the t-table = 2.034 was obtained. So the t-count is greater than the t-table, so in this case Ho is rejected and Ha is accepted. This means that there is a real influence between the completeness of learning facilities on the science learning outcomes of grade VII students of SMP N.10 Pematangsiantar. Based on the results of the determination test, the contribution of the completeness of learning facilities to the science learning outcomes of seventh-grade students at SMP N 10 Pematangsiantar was 65.61%. This means that students' science learning outcomes are influenced by the completeness of learning facilities. It was concluded that there is a significant influence between the completeness of learning facilities and the science learning outcomes of seventh-grade students at SMP N 10 Pematangsiantar in the 2021/2022 academic year.